Characteristics and outcomes of patients requiring airway rescue by the difficult airway response team in the emergency department and wards: A retrospective study - Ting-Sian Yu (Tzu-Chi Medical Journal, 2020)
Objective: In this retrospective cohort study, we aimed to determine the characteristics and outcomes of patients in the emergency department (ED) and wards who required emergency tracheal intubation by the difficult airway response team (DART). Materials and Methods: All patients between 18 and 80 years old receiving emergency tracheal intubation by the DART at a single tertiary referral hospital from January 2014 to December 2016 were reviewed and divided into ward and ED groups. Patient characteristics, comorbidities, indications for intubation, airway maintenance technique, and survival-to-discharge rates were analyzed and compared. Results: Totally, 192 patients (ward, n = 135; ED, n = 57) were eligible for the current study. Compared with the ward group, patients in the ED group were younger (58.9 ± 13 vs. 51.5 ± 15.6 years, P = 0.001), male-predominant (71.1% vs. 87.7%, P = 0.014), and had a higher incidence of trauma (6.7% vs. 22.8%, P = 0.001). The most common indications for tracheal intubation were respiratory distress (52.6%) and cardiac arrest (17.8%) in the ward group, and respiratory distress (31.6%) and airway protection (28.1%) in the ED group. Patients in the ED group received more fiberoptic intubations (42.1% vs. 17.8%, P = 0.039) and had a higher survival-to-discharge rate (87.7% vs. 44.4%, P < 0.001) than those in the ward group. Conclusions: Better recognition of differences in patient characteristics and indications for intubation in different units of the hospital may enable the DART to customize specialized equipment to improve efficiency and implement appropriate strategies for airway rescue to improve patient outcomes.